Gender-related differences in psychometric properties of WHO Disability Assessment Schedule 2.0 - Katajapuu N.; Laimi K.; Heinonen A.; Saltychev M. (NLM (Medline), 2022)
Objective of this study was to investigate the gender-related differential item function of 12-item WHODAS 2.0 amongst patients with chronic musculoskeletal pain. This was a cross-sectional survey study among 1,988 patients at a university Physical and Rehabilitation Medicine outpatient clinic. To assess DIF, WHODAS 2.0 items were dichotomized as `none’ rated by respondents as `0’ versus `any limitation’ rated as `1,2,3 or 4’. The item response theory analysis was used to define discrimination and difficulty parameters of a questionnaire. The probit logistic regression was used to test uniformity of DIF between gender groups. The results of DIF analysis were presented and evaluated graphically as item characteristic curves based on 2-parameter IRT analysis of dichotomized responses. High to perfect discrimination ability was observed for all the items except one. Difficulty levels of eight items were shifted towards the elevated disability level, four items demonstrated a perfect difficulty property. Significant DIF between genders was observed in seven of 12 items. The detected DIFs were uniform. For item `household’, `emotional affection’ and `work’, men had to experience slightly worse disability than women to achieve the same score. A reverse effect was observed for items `concentration’, `washing’, `dressing’ and dealing with strangers. In this study, significant DIF between genders was found in seven of twelve items of 12-item WHODAS 2.0. amongst 1988 patients with chronic musculoskeletal pain. All the detected DIFs were uniform. Regardless gender-related DIF shown in seven out of 12 items, we recommend using and studying 12-item WHODAS 2.0 in different populations.